The Application of Phonics Instruction in Reading Text at Grade X SMK N.1 Pematangsiantar - Ruth Aprilia Manullang; Ester Sianipar; Herman; Bloner Sinurat (Periodica Journal, 2022)
This research is concerned with finding the types of phonics used by teachers and students when learning English in the classroom. The problem discussed was: What types of phonics instruction are used in reading text at grade X of SMK Negeri 1 Pematangsiantar. This research focused to the four kinds of phonics, they are: The Sinthetic phonics, Analytic phonics, Analogy phonics, Embedded phonics. This research used the qualitative research. The subject of this research in grade X SMK Negeri 1 Pematangsiantar are the English teacher and students. Here, the researchers took 15 students. The students in the class are male and female. Some steps taken in collecting the data were reading text from students’ reading material, recording the phonics instructions used by the teacher in teaching the reading material, and identifying all types of phonics instructions used by the teacher in teaching the reading material as the research data. After that, the researchers did analysis to the data which covered: identifying the types of phonics instructions, classifying, calculating the frequency of phonics and drawing conclusion. The finding shows that the reception of students to the model was good and they showed much eagerness in following the program. Further investigation revealed that students keen to participate more in the classroom activities.
Keywords: Application; Phonics Instruction; Reading Text